MITIGASI COVID-19 DALAM RUANG LINGKUP ISO 45001 MENGHADAPI ERA ADAPTASI BARU - Utami, Desyawati (Universitas Esa Unggul, 2020)
Occupational Health and Safety Management System based on ISO 45001 provides a framework for its organization to maintain OHS performance through pandemic situation. It scope is designed to organization for doing preventive actions in order to reduce incident and occupational disease. This system is bringing a dynamic workflow for organization in create its actions regarding risks and opportunites. The scope of this program is both businessman and workers in facing the new normal. Method of its program is socializing the material course with online using zoom platform hosted by LPPM-Esa Unggul University. The result of the questioners is 73,87% for its all understanding. Summary of this program is the participants is good in understanding of OHS Management System concept but lack of understanding of High Level Structure.Â Keywords: Mitigation of Covid-19, ISO 45001, New Normal.